Human relationship skills : training and self-help - Nelson-Jones, Richard, 1936- (London : Cassell, 1990)
In this edition there are chapters on choosing relationships, on strengthening them and on what the reader brings to a relationship, as well as those on how skills can be learnt, encouraging readers to accept responsibility for developing them and putting them into practice.
Previous ed.: London : Holt, Rinehart and Winston, 1986.
Bibliography: p309-317. - Includes index.
Keywords: Interpersonal relations